Effects of the Reynolds number and the tip losses on the optimal aspect ratio of straight-bladed Vertical Axis Wind Turbines. (1st April 2018) - Zanforlin, Stefania; Deluca, Stefano
Abstract: Aspect Ratio ( AR ) is one of the main design parameters of straight-bladed vertical axis turbines. This paper will examine whether a high AR, with long blades and low tip losses, or a low AR, with a higher diameter and higher losses, is more suitable to achieve the maximum power output given a fixed cross-sectional area. Traditional Double-Multiple Stream-Tube (DMST) approaches are limited by a lack of tip loss formulations specifically conceived for vertical axis turbines. Therefore, a CFD-3D investigation covering a power range from micro-generation to MW has been done. Results show that both Reynolds number and tip losses strongly influence the aerodynamic performance of the rotor. More advantages seem to be achieved by limiting tip losses rather than increasing chord-based Reynolds number ( Re c ), addressing towards high AR at least for medium and large-size turbines. However, as turbine size and wind speed decrease, this difference narrows considerably. For micro turbines, tip losses are balanced by the effects of Re c, thus a variation of AR does not imply a variation of C P . For all the cases that have been analysed, turbine size and therefore Re c does not appreciably affect the normalized C P distribution along the blade, which only depends on AR . Highlights: The study analyses different ARs from micro-generation to MW by means of CFD-3D. Performance of high ARs turbines are more influenced by tip losses than Rec . For smaller turbines, tip losses effects are compensated by Rec effects. To reduce flow separation in small turbines under slow wind, higher TSR is required. The normalised CP distribution along the blade only depends on AR, not on Rec .